2013
DOI: 10.2511/027494813807714474
|View full text |Cite
|
Sign up to set email alerts
|

Does Providing Transition Services Early Enable Students with ASD to Achieve Better Vocational Outcomes as Adults?

Abstract: This study investigated whether receiving transition services early (i.e., by age 14) promoted better vocational outcomes than receiving transition services later (i.e., by age 16) for young adults with ASD. To do this, the outcomes achieved by two matched groups were examined—453 young adults from states requiring transition services be addressed by age 14 and 453 young adults with ASD from states requiring transition services be addressed by age 16. In each of the four years examined (i.e., 2006–2009), indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 13 publications
(16 reference statements)
1
33
0
1
Order By: Relevance
“…23 This is a critical gap in the autism literature, considering the United States spends roughly $130 billion annually on services for people with autism. 51 In addition to the reviewed study about state-mandated transition policies, 23 research on children with special health care needs 52 has also revealed how we can learn policy-relevant lessons by comparing outcomes across states. Our eighth research recommendation is to examine how mutable policy factors are associated with variability in TAY outcomes.…”
Section: Policy Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…23 This is a critical gap in the autism literature, considering the United States spends roughly $130 billion annually on services for people with autism. 51 In addition to the reviewed study about state-mandated transition policies, 23 research on children with special health care needs 52 has also revealed how we can learn policy-relevant lessons by comparing outcomes across states. Our eighth research recommendation is to examine how mutable policy factors are associated with variability in TAY outcomes.…”
Section: Policy Levelmentioning
confidence: 99%
“…The authors of 15 studies drew from the National Longitudinal Transition Study-2, * the authors of 2 studies used the National Survey of Children with Special Health Care Needs, 20,30 and the authors of 1 study used the Rehabilitation Services Administrative Case Services Report. 23 The authors of the remaining 2 studies directly recruited families of adults with autism. 34,35 Sample sizes ranged from 39 to 17 818 people.…”
Section: Sample Characteristics and Methodological Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-initiated services provide longer time for individual preparation and navigation, and young adults with ASD can become more skilled and employable for employment after exiting the school system (Autism Speaks 2012; Chappel and Somers 2010;Hendricks and Wehman 2009). Cimera et al (2013) analyzed 4-year vocational rehabilitation data and found quite compelling results. The study showed that individuals with ASD who received transition services at age 14 were significantly more likely to be employed than those who received transition services at age 16.…”
Section: Transition Servicesmentioning
confidence: 99%
“…In the study, a group initiated a transition programme starting from the age of 16 while another group started at the age of 14. The study found that the groups who started the transition programme earlier than 14 years are able to get jobs easier after they completed schooling (Cimera, Burgess, & Wiley, 2013). Due to that, this study aims to review the implementation of transition programme among students with learning disabilities at schools; review how vocational training is provided to the students;…”
Section: Introductionmentioning
confidence: 99%